2015 IEEE International WIE Conference on Electrical and Computer Engineering (WIECON-ECE) 2015
DOI: 10.1109/wiecon-ece.2015.7443951
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of human emotion with effective frequency band during a test of sustained mental task

Abstract: Modeling of human emotion with the effective frequency band of EEG signal plays a significant role in brain signal analysis and physiological research area. This paper describes an approach to model human emotion with the variations of different effective frequency bands of EEG signal during a test when subjected to sustained mental task. For this purpose, the EEG signals are collected when different types of mental task were performed. During a test the subjects were asked to read the text or mathematical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Overall, the average alpha and beta values in the experimental condition were significantly higher than those in the control condition. Our results suggest that the fragrant Primula induced a stronger physiological and psychological effect, which reflects emotional relaxation and improved attention ( Islarn and Ahmad, 2015 ). It suggested that olfaction benefited neural activity in a unique way, which could not be achieved by visual stimuli alone.…”
Section: Discussionmentioning
confidence: 79%
“…Overall, the average alpha and beta values in the experimental condition were significantly higher than those in the control condition. Our results suggest that the fragrant Primula induced a stronger physiological and psychological effect, which reflects emotional relaxation and improved attention ( Islarn and Ahmad, 2015 ). It suggested that olfaction benefited neural activity in a unique way, which could not be achieved by visual stimuli alone.…”
Section: Discussionmentioning
confidence: 79%
“…In his study, both the alpha and beta waves are active during a workload, and when the workload on the brain increases, beta wave activity then increases. e study shows that when people use more focus on a specific task, the ratio of the beta power increases [48]. Additionally, beta waves are fast wave activity and are used to engage in decision making and mental tasks [49] such as attending lectures in a classroom or solving problems.…”
Section: Discussionmentioning
confidence: 99%